Research of two-phase excitation and stator winding mode of switched reluctance motor - LIU Chengyao; PAN Zaiping (Gong-kuang zidonghua, 2016)
The paper took 4/6 poles three-phase switched reluctance motor and 6/8 poles four-phase switched reluctance motor as study objects, analyzed influence of winding structure and phase connection way of three-phase and four-phase switched reluctance motor on magnetic field, torque ripple and average torque under two-phase excitation, gave motor torque characteristics of two-phase excitation under eight typical combination modes, and pointed that two-phase excitation under modes of three-phase reverse winding with independent connection of each phase, three-phase positive winding with star connection of each phase, four-phase reverse winding with independent connection of each phase and four-phase reverse winding with star connection of each phase could reduce torque ripple and improve average torque.